THE DIRECTION OF CENTRAL ASIA IN UZBEKISTAN’S FOREIGN POLICY - Abdusamat Abdukhalilov (International Scientific and Current Research Conferences, 2022)
This article discusses the direction of Central Asia in Uzbekistan’s foreign policy. Despite the threat of a global pandemic, the leaders of the Central Asian countries maintained constant dialogue and continued active cooperation between the countries. The countries of the region began to provide social assistance to each other from the first days of the spread of the coronavirus infection. Uzbekistan sent humanitarian aid to Kazakhstan, Kyrgyzstan and Tajikistan several times.